2020
DOI: 10.1002/jcp.29588
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin‐like 1: A dual regulator that promotes cardiomyocyte proliferation and fibrosis

Abstract: Follistatin-like 1 (FSTL1) is a key factor in maintaining cardiac growth and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…It was further confirmed that FSTL1 delivered through an epicardial patch protected the heart against MI injury by promoting cardiomyocyte division ( Wei et al, 2015 ). Further, FSTL1 protected the heart against MI injury by decreasing myocardial fibrosis, and protected the heart from rupture by regulating cardiac fibroblast activation ( Rainer et al, 2014 ; Maruyama et al, 2016 ; Xiao et al, 2019 ; Hu et al, 2020 ). Importantly, upregulation of FSTL1 secretion induced by exercise training alleviated cardiac dysfunction resulting from MI injury by TGFβ-Smad2/3 induced angiogenesis ( Xi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was further confirmed that FSTL1 delivered through an epicardial patch protected the heart against MI injury by promoting cardiomyocyte division ( Wei et al, 2015 ). Further, FSTL1 protected the heart against MI injury by decreasing myocardial fibrosis, and protected the heart from rupture by regulating cardiac fibroblast activation ( Rainer et al, 2014 ; Maruyama et al, 2016 ; Xiao et al, 2019 ; Hu et al, 2020 ). Importantly, upregulation of FSTL1 secretion induced by exercise training alleviated cardiac dysfunction resulting from MI injury by TGFβ-Smad2/3 induced angiogenesis ( Xi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…If there has a therapeutic strategy that can balance this pathological change? Previous studies have suggested that FSTL1 attenuated pathological injury of multiple organs by alleviating fibrosis, particularly in cardiac dysfunction ( Jiang et al, 2020 ; Hu et al, 2020 ; Li et al, 2021 ; Z.; Chen Z. et al, 2019 ; Yang et al, 2020 ). Our current findings are consistent with these aforementioned research findings that the upregulation of FSTL1 in DM compared with the control group, which was further increased in T2DM with MI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the factors related to the myocardial repair, several growth factors [35,36] have been found to promote the proliferation of cardiomyocytes, but they have the risk to cause cardiac fibrosis. microRNAs [7,11] also show effects in stimulated cardiomyocytes proliferation in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It manifests as deposition of scar, increasing stiffness, decreasing contraction and impaired heart function, which ultimately resulting in heart failure (116). Although, cardiac fibrosis is a complex process and involves many types of cells in the heart, such as cardiomyocytes, fibroblasts, lymphocytes, and pericytes (117)(118)(119), extensive studies have proved that cardiac fibroblasts (CFs) play a pivotal role in this process (120). When suffered cardiac injury, the proliferation and migration of CFs are increased.…”
Section: Circular Rnas In the Activation Of Cardiac Fibroblastsmentioning
confidence: 99%